Involvement of HIF-1α-regulated miR-21, acting via the Akt/NF-κB pathway, in malignant transformation of HBE cells induced by cigarette smoke extract. (1st June 2018) - Lu, Lu; Xu, Hui; Yang, Ping; Xue, Junchao; Chen, Chao; Sun, Qian; Yang, Qianlei; Lu, Jiachun; Shi, Aimin; Liu, Qizhan
Highlights: CSE increases miR-21 levels, which are regulated by HIF-1α. MiR-21, acting via inhibition of PTEN, modulates the Akt/NF-κB pathway. HIF-1α-regulated miR-21, acting via the Akt/NF-κB pathway, is involved in the EMT of CSE-transformed HBE cells. Abstract: Although the relationship between cigarette smoke and lung cancer has been widely studied, the molecular mechanism for cigarette smoke-induced lung cancer remains largely unclear. The present study investigated the roles of hypoxia-inducible factor (HIF)-1α and miR-21 in the malignant transformation of human bronchial epithelial (HBE) cells induced by cigarette smoke extract (CSE). In case of acute and chronic treatment of HBE cells, CSE increased the levels of HIF-1α, p-Akt, p-NF-κB, and miR-21 and decreased PTEN levels. The increased miR-21 levels induced by CSE were prevented by down-regulation of HIF-1α. Further, elevated miR-21 suppressed PTEN levels, which decreased the levels of p-Akt and p-NF-κB. However, those changes were attenuated in cells co-transfected with HIF-1α siRNA and an miR-21 mimic. Silencing of HIF-1α or NF-κB decreased colony formation and the invasion and migration capacities of CSE-transformed HBE cells; however, up-regulation of miR-21 reversed these effects. These results indicate that the oncogenic capacity of HIF-1α in regulation of miR-21-inhibited PTEN in a manner dependent on the Akt/NF-κB pathway, a process that is involved in the CSE-induced malignant transformation of HBE cells. Thus, the present research has established a new mechanism for cigarette smoke-induced lung carcinogenesis.